Firenze, archeologia di una città (secoli I a.C. - XIII d.C.) - Scampoli, Emiliano (Strumenti per la didattica e la ricerca, 2010)
The urban evolution of Florence in the first thirteen centuries of its history is delineated here via a census of the archaeological finds, starting from those documented in the second half of the nineteenth century. The information has been organised and analysed through the use of Geographic Information Systems. The finds have been broken down by period and in terms of function, so as to describe, where possible, the evolution of the buildings and the public spaces and the changes in ways of living and approaches to burial, defence and production over the course of time. The Florentine data are considered within the regional and Italian framework mapped by archaeological research over the last few decades. Theme maps created using GIS further enhance the understanding of the text.